Characterization of the novel HLA‐A*24:538 allele by sequencing‐based typing. (17th August 2021) - Cargou, Marine; Elsermans, Vincent; Top, Isabelle; Ralazamahaleo, Mamy; Visentin, Jonathan
ABSTRACT: HLA‐A*24:538 differs from HLA‐A*24:02:01:01 by one nucleotide substitution in codon −21 in exon 1.